2020
DOI: 10.1186/s12944-020-01392-7
|View full text |Cite
|
Sign up to set email alerts
|

LDL-C/HDL-C is associated with ischaemic stroke in patients with non-valvular atrial fibrillation: a case-control study

Abstract: Background This study explored the relationships between the low−/high-density lipoprotein cholesterol ratio (LDL-C/HDL-C) and other clinical indicators and ischaemic stroke (IS) in patients with non-valvular atrial fibrillation (NVAF) in Xinjiang. The findings could provide a theoretical and therapeutic basis for NVAF patients. Methods NVAF patients who were admitted to 10 medical centres across Xinjiang were divided into stroke (79… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 59 publications
0
14
0
Order By: Relevance
“…Moreover, prospective cohort study has demonstrated that LDL-C/HDL-C ratio can serve as the potent predictor of all-cause mortality in elderly hypertensive patients ( 35 ). The LDL-C/HDL-C ratio has also been reported as an independent risk factor for ischemic stroke in non-valvular atrial fibrillation ( 36 ). As for the TG/HDL-C ratio, novel findings suggest that it can be used as a marker of insulin resistance ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, prospective cohort study has demonstrated that LDL-C/HDL-C ratio can serve as the potent predictor of all-cause mortality in elderly hypertensive patients ( 35 ). The LDL-C/HDL-C ratio has also been reported as an independent risk factor for ischemic stroke in non-valvular atrial fibrillation ( 36 ). As for the TG/HDL-C ratio, novel findings suggest that it can be used as a marker of insulin resistance ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore HDL-C-mediated protection remains controversial. Studies have proved that LDL-C/HDL-C is closely related to the onset of CHD and the progression of atherosclerosis [ 4 , 26 , 27 ]. A prospective study showed that the LDL-C/HDL-C predicted the progress of CIMT better than HDL-C or LDL-C alone [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore HDL-C protection is still controversial [20] . Studies proved that the LDL-C/HDL-C was closely related to the onset of CHD and the progression of atherosclerosis [21][22][23] . A prospective study showed that the LDL-C/HDL-C predicted the progress of CIMT better than HDL-C or LDL-C alone [24] .…”
Section: Discussionmentioning
confidence: 99%